Fenomena Natural Resource Curse dalam Pembangunan Wilayah di Indonesia - Rahma, Hania; Fauzi, Akhmad; Juanda, Bambang; Widjojanto, Bambang (UI Scholars Hub, 2021)
Although the phenomenon of natural resource curse is suspected to have occurred at the regional level in Indonesia, no measurement of such a phenomenon has been carried out yet. This research is aimed to provide an index of measuring the degree of natural resource curse at provincial level in Indonesia. Two indices, the natural resource dependence index and regional sustainable development index, were used to formulate index of regional resource curse (RRCI) using geometric mean of conditional weighted product method. The results found that provinces with richer in mining tend to have higher resource curse index compared with those with less extractive resources.